Cost-effective microwave-assisted O3- type sodium-based layered oxide cathode materials for sodium-ion batteries - R.A. Harindi Gayara; Buzaina Moossa; R.A. Shakoor; Rana Faisal Shahzad; Muhammad Sajjad; Nirpendra Singh; Shahid Rasul; Talal Mohammed Al tahtamouni (Energy Reports, 2023)
In this work, phase pure and highly crystalline O3-type layered oxide material (Na1Ni0.33Mn0.33Fe0.33O2-NNMF) was developed using; (i) a conventional solid-state synthesis route and (ii) a facile microwave-assisted sol–gel technique. A comparison of structural, thermal, and electrochemical properties is presented to elucidate the usefulness of the microwave-assisted sol–gel synthesis technique. A remarkable reduction in the sintering process time is noticed in the microwave-assisted sol–gel synthesis technique without compromising on the structural, thermal and electrochemical properties when compared to the conventional solid-state synthesis route confirming its decent cost-effectiveness. It is further noticed that NNMF developed through microwave-assisted sol–gel synthesis technique demonstrates superior thermal stability and comparable electrochemical performance as compared to the same material produced through the conventional sintering process. The decent electrochemical properties induced in NNMF during the microwave-assisted sol–gel synthesis technique can be attributed to the efficient diffusion of Na+ ions into/from the host structure during the intercalation/de-intercalation process as indicated by the high value of sodium diffusion coefficient (1 × 109-3.58 × 109m2s−1). The Potentiostatic Intermittent Titration Technique (PITT) analysis confirms single-phase Na+ intercalation/deintercalation in the host structure, regardless of the synthesis process. Finally, EIS analysis confirms the capacity fading of the developed materials during the cycling process is essentially due to an increase in the resistance with the increasing number of cycles due to the gradual thickening of formed SEI layer. The microwave-assisted sol–gel synthesis technique can be effectively employed for the production of many families of cathode materials at competitive cost facilitating their commercialization.